Action recognition using optimized deep autoencoder and CNN for surveillance data streams of non-stationary environments - Ullah, Amin; Muhammad, Khan; Haq, Ijaz Ul; Baik, Sung Wook (Future generation computer systems, 2019)
Action recognition is a challenging research area in which several convolutional neural networks (CNN) based action recognition methods are recently presented. However, such methods are inefficient for real-time online data stream processing with satisfied accuracy. Therefore, in this paper we propose an efficient and optimized CNN based system to process data streams in real-time, acquired from visual sensor of non-stationary surveillance environment. Firstly, frame level deep features are extracted using a pre-trained CNN model. Next, an optimized deep autoencoder (DAE) is introduced to learn temporal changes of the actions in the surveillance stream. Furthermore, a non-linear learning approach, quadratic SVM is trained for the classification of human actions. Finally, an iterative fine-tuning process is added in the testing phase that can update the parameters of trained model using the newly accumulated data of non-stationary environment. Experiments are conducted on benchmark datasets and results reveal the better performance of our system in terms of accuracy and running time compared to state-of-the-art methods. We believe that our proposed system is a suitable candidate for action recognition in surveillance data stream of non-stationary environments. •Action recognition in online data stream acquired from non-stationary surveillance.•Efficient CNN model is used for frame-level representation.•An optimized deep autoencoder is presented for learning sequences and squeezing high. dimensional features.•Investigated a non-linear learning approach for action recognition.•Iterative fine-tuning of the trained recognition model for newly accumulated data.